1983
DOI: 10.1111/j.1399-3054.1983.tb04149.x
|View full text |Cite
|
Sign up to set email alerts
|

Indole‐3‐methylglucosinolate biosynthesis and metabolism in clubroot diseased plants

Abstract: lndole‐3‐methylglucosinolate biosynthesis and metabolism in roots of Brassica napus (swede, cv. Danestone II) infected with Plasmodiophora brassicae Wor. were investigated with a pulse feeding technique developed to infiltrate intact tissue segments with labelled substrates. Infected root tissue metabolized [14C]‐L‐tryptophan to indole‐3‐methylglucosinolate, indole‐3‐acetonitrile, and some other lipophilic indole compounds. The incorporation of radioactivity into these compounds was significantly enhanced in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 26 publications
(25 reference statements)
1
24
0
1
Order By: Relevance
“…Already early work on clubroot showed that during clubroot formation, an increased synthesis and turnover of the putative host auxin precursors (see Fig. 2) indole-3-acetaldoxime (IAOx), indole-3-methylglucosinolate (indole GSL) and indole-3-acetonitrile (IAN) have been detected in infected Brassica rapa roots (Searle et al 1982;Rausch et al 1983;Butcher et al 1984). Based on this experimental evidence it was hypothesized that if the indole GSL are key factors for the biosynthesis of IAA in clubs, then plants having little or no indole glucosinolates, and as a result less auxin, might be resistant to clubroot or should develop less severe symptoms (Butcher et al 1974).…”
Section: Auxins and Indole Glucosinolatesmentioning
confidence: 96%
“…Already early work on clubroot showed that during clubroot formation, an increased synthesis and turnover of the putative host auxin precursors (see Fig. 2) indole-3-acetaldoxime (IAOx), indole-3-methylglucosinolate (indole GSL) and indole-3-acetonitrile (IAN) have been detected in infected Brassica rapa roots (Searle et al 1982;Rausch et al 1983;Butcher et al 1984). Based on this experimental evidence it was hypothesized that if the indole GSL are key factors for the biosynthesis of IAA in clubs, then plants having little or no indole glucosinolates, and as a result less auxin, might be resistant to clubroot or should develop less severe symptoms (Butcher et al 1974).…”
Section: Auxins and Indole Glucosinolatesmentioning
confidence: 96%
“…However, increase in indole-3-acetic acid (IAA; auxin) levels in infected roots might result from increased synthesis and/or turnover of the putative host auxin precursors (Butcher et al 1974;Rausch et al 1981Rausch et al , 1983Searle et al 1982). Several studies have indicated that auxin levels increase in clubbed roots (Raa 1971;Butcher et al 1974;Ludwig-Müller et al 1993, 1999Ugajin et al 2003;Devos et al 2005), although most of these studies have indicated complicated changes in the time course.…”
Section: Introductionmentioning
confidence: 95%
“…Ludwig-Muller and Hilgenberg (19) found a formation rate for individual indole derivatives of 4 to 13% of total radioactivity uptake after feeding of N-DL-malonyltryptophan to segments of Chinese cabbage. Helmlinger et al (18) found rates of 8 to 15% for the conversion of indole-3-acetaldoxime to indole-3-acetonitrile in Chinese cabbage, while Rausch et al (23) determined rates of approximately 3% in benzenesoluble products and approximately 12% in water-soluble products after feeding of tryptophan to segments of Brassica napus. The low Km value for the conversion of IAA to IBA, indicating high affinity for the substrate IAA (Fig.…”
Section: Identification Of the Reaction Productmentioning
confidence: 99%